Dracaena cochinchinensis stemwood extracts inhibit amyloid-β fibril formation and promote neuronal cell differentiation - Dusadee Ospondpant; Dusadee Ospondpant; Xiong Gao; Xiong Gao; Tina Tingxia Dong; Tina Tingxia Dong; Karl Wah Keung Tsim; Karl Wah Keung Tsim (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by the deposition of amyloid plaques in the brain. The prevention of amyloid-β (Aβ)-induced neuronal toxicity is considered a major target for drug development for AD treatment. Dracaena cochinchinensis (Lour.) S.C. Chen, a Thai folk medicine named “Chan-Daeng,” is a member of the Asparagaceae family. The stemwood of D. cochinchinensis has been traditionally used for its antipyretic, pain relief, and anti-inflammatory effects. The aim of the present study was to determine the pharmacological activities of ethanol and water extracts of D. cochinchinensis stemwood in blocking the Aβ fibril formation, preventing Aβ-mediated cell toxicity, and promoting neuronal differentiation in cultured PC12 cells. The herbal extracts of D. cochinchinensis stemwood prevented the formation of Aβ fibrils and disassembled the aggregated Aβ in a dose-dependent manner. Additionally, they prevented Aβ fibril-mediated cell death. The synergy of the herbal extract with a low dose of the nerve growth factor showed an increase in the protein expression of neurofilaments, that is, NF68, NF160, and NF200. These findings suggest that the extracts of D. cochinchinensis stemwood may be used for AD treatment by targeting Aβ fibril formation and inducing neuron regeneration.